Project review for the Pufendorf Institute for Advanced Studies, Sweden - Assis, Paulo de (2023)
Sound of Democracy—How everyday sound environments support, reflect and deflect democratic values.Through the use of sound this project investigates democratic values, and their manifestation in sound environments. Research on democracy investigates questions such as: How is power allocated between different actors? or How is expert knowledge democratized? We will examine everyday examples of how this allocation and democratization works. Sound is an inevitable consequence of actions and relations in our world, and all spaces have an acoustic element to them. At the same time, questions of democracy in relation to everyday life—inclusion in, access to, equality of— play out across society in legislation, sustainable development, higher education and academic freedom. In terms of actual results of democratic goals, sound has a particularly disobedient quality—it does not obey visual, legal or ownership borders. The theme’s main research question is how everyday sound environments support, reflect and deflect democratic values. Everyday effects, and use of sound, dissolve and disrespect disciplinary boundaries where sound is forming its own territory and rules. Through our investigations it will be possible to identify Sonic Actants (types, roles) and Ambiguous Sounds in order to achieve an understanding of various sounds, and their surrounding situations connected to democratic values. Artistic research holds a methodological potential that crosses disciplinary boundaries, this will be used through introducing kaleidoscopic hearing that activates an ‘intense empathy’, and can thereby interrogate democratic values in an immediate sense through an emotional response to the question: What does this sound make me feel? This involves forming new knowledge on how sound, and its uses, may be democratized. In this project, sound is both involved as the key theoretical component and as a methodological element that crosses boundaries through experimental and collective perception of sound environments, this will contribute to the discussion and visibility of structures of equality, justice and inclusion.
FRIS
1
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music